Research on Space Systemization and Reduction of Examination Time of Medical Checkup Centers Applying the Agent -based Model - Kim, Suktae; ., . (International Journal of Engineering and Technology, 2019)
Modern medicine is changing from centering on treatment to prevention and from patients to the general public, and medical checkup centers, which until recently were merely attachments to the hospitals, are becoming increasingly significant independent medical facilities. Since medical facilities can provide services in more adverse conditions than other facilities, the waiting times and cognitive spatial environment are more crucial than in any other facility. However, because extremely purpose-oriented medical facilities have become very complex when considering usersâ€™ behavioral factors, analysis with existing space theory has its limits. Hence, discrete-event simulation, a complex network analysis theory, was applied to spatial analysis to check for possibilities for efficiency improvement. The study was carried out by getting the spaceâ€™s structural characteristics using space syntax, setting up the standard checkup program and the sample space, programming in the assessment factors such as the number of people on the waitlist (maximum and average) and both the survival duration and distribution of agents into the pedestrian-based discrete-event simulation analysis tool, and using it to determine the maximum capacity of users and related problems.On the premise that the costs are kept to a minimum, corrective measures were changed, the redistribution of some roomsâ€™ purposes and services were prepared, and the new planâ€™s improved efficiency compared to that of its predecessor has been proven through simulations and analyses. According to the simulations, the walking distance was shortened and the path networkâ€™s structure was simplified, which led to enhanced structural cognition of the space and, thus, reduced the average checkup time by 46 minutes and the maximum time required for 50 checkups by 52 minutes, resulting in increased patient occupancy by 10â€“20 persons with little effort and cost. Even though the results of this research were from relatively small checkup centers, it proves that complex network analysis applying discrete-event simulation to a space can be effectively utilized as an architectural tool for structurally designing medical facilities, including checkup centers. Applying it at an early blueprinting stage as a preliminary simulation tool maximizes its effectiveness and is expected to be compatible with large-scale, complex facilities.Â Â